Perceived Parent Needs for Improving Parent Participation in School-Based Therapies for Children with Disabilities Using the Parent-Therapist Partnership Survey. - Murphy, Ashley N.; Moskowitz, Kathleen; Fernandez, Francesca; Risser, Heather J. (Journal of Autism & Developmental Disorders, 2025)
Rehabilitative and habilitative therapies can help children with disabilities increase independence and overall wellbeing. However, children and their caregivers face many barriers to accessing these therapies and often rely on the school for therapy access. Given the limited resources available within the special education system, increasing parent involvement in special education therapies could improve service delivery. However, providers must first understand what parents need to participate in therapies before attempting to engage families. 217 parents completed an online survey consisting of the Parent-Therapist Partnership Survey and demographic questionnaires about theirfamiliesand their child[ren] with disabilities. The percentage of needs parents endorsed as important and thepercentageofimportantneedsendorsedasunmetwere calculated. Differences across demographic variables were assessed. Overall, parents reported an average of 75% of needs as important with significantly more needs endorsed as important regarding being an informed, engaged member of the child's care team (M = 83%) than needs related to support and guidance (M = 65%, p < 0.001). Furthermore, parentsreportedan average of 58% of important needs as unmet, with no significant differences in subscale averages. Significant associations were found for race/ethnicity, education, income, partner availability, number of children with disabilities in the household, transportation access, neighborhood opportunities, parent efficacy and social, emotional, and behavioral concerns. Parents reported a high percentage of needs as important, but a large percentage of these important needs were considered unmet. Significant disparities based on racial/ethnic identities and access to resources were found. In order to successfully engage parents in special education therapy activities, providers must work to understand and address parents' engagement needs, paying special attention to each family's unique circumstances to optimize engagement.